2020
DOI: 10.1038/s41598-020-61814-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of scaling on aeration performance of fine-pore membrane diffusers based on a pilot-scale study

Abstract: Aeration systems consume a large amount of energy in wastewater treatment plants. Fine-pore membrane diffusers are most commonly used in aeration systems. Scaling and fouling on these membrane diffusers will lead to decreased performance in aeration and increase energy consumption. This pilot-scale study focused on the scaling of the three kinds of fine-pore membrane diffusers under different influent hardness conditions. The results showed that the diffusers were mainly polluted by calcium carbonate scaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Since the MVA circulates and supplies pure oxygen, it was confirmed that the MVA increases dissolved oxygen concentrations to higher levels in a shorter time than other existing aeration devices, such as fine pore diffusers. Fine pore diffusers suffer from the drawbacks of inorganic scaling and biological fouling, which can reduce the transfer efficiency and cause excessive head loss [20].…”
Section: Multistage Vortex Aerator (Mva)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the MVA circulates and supplies pure oxygen, it was confirmed that the MVA increases dissolved oxygen concentrations to higher levels in a shorter time than other existing aeration devices, such as fine pore diffusers. Fine pore diffusers suffer from the drawbacks of inorganic scaling and biological fouling, which can reduce the transfer efficiency and cause excessive head loss [20].…”
Section: Multistage Vortex Aerator (Mva)mentioning
confidence: 99%
“…Since the MVA circulates and supplies pure oxygen, it was confirmed that the MVA increases dissolved oxygen concentrations to higher levels in a shorter time than other existing aeration devices, such as fine pore diffusers. Fine pore diffusers suffer from the drawbacks of inorganic scaling and biological fouling, which can reduce the transfer efficiency and cause excessive head loss [20]. In addition, although the conventionally used oxygenators use the 21% of oxygen in the air as an oxygen source, there is a limit to the movement speed of oxygen, whereas the multistage vortex aerator uses high-purity oxygen (about 90% oxygen).…”
Section: Multistage Vortex Aerator (Mva)mentioning
confidence: 99%